MBE growth and abnormal magnetic behaviors of epitaxial Fe100−xGax on SrTiO3 - Thi Toan Tran; Thi Hoa Vu; Anh Tuan Pham; Thi Huong Nguyen; Van Quang Nguyen; Chanyong Hwang; Sunglae Cho (AIP Advances, 2023)
Here, we present the magnetic behaviors of disordered bcc α-Fe phase Fe100−xGax (x = 10, 20, and 30) thin films grown on a SrTiO3 substrate using molecular beam epitaxy. With the Ga content increasing from 10% to 30%, the saturation magnetization decreased from 1575 to 991 emu/cm3 while the coercivity increased from 23 to 197 Oe. A two-step-hysteresis loop was observed in all films. Specifically, the hysteresis loop of the film with 10% Ga concentration reveals an obvious kink. Magneto-optical Kerr images confirmed the abnormal magnetic domain switching in the films, which is due to the appearance of perpendicular domains under external magnetic field.